Reference desk service: success or failure? - Norazlin H.; Che Rusuli M. S.; Tasmin R.; Norliya Ahmad Kassim; Alhaji Abubakar Aliyu (2015)
At present, research related to library user satisfaction is a never ending journey. With this regard, this study seeks to assess the reference desk services and the users’ satisfaction level at Malaysian academic libraries. Twenty respondents from Perpustakaan Tun Abdul Razak Library (PTAR), Universiti Teknologi Mara (UiTM) Shah Alam and Perpustakaan Tunku Tun Aminah Library (PTTA), Universiti Tun Hussein Onn Malaysia Johor was involved in this study. The result revealed that students of both libraries expressed the needs of services rendered by the reference desk, in terms of the usage and importance of the reference desk. Specifically, UTHM students preferred and online information searching compared to UiTM students. This means that, libraries can provide specific services to students who underutilized the reference desk. Hence, this study is used to seek whether reference desk services are still relevant (success) or not (failure) when experiencing declining reference desk services from the students’ perspective. It is hoped that the findings of this study will be beneficial for increasing level of user satisfaction in order to retain reference desk services in the library.